Manajemen Strategi Pemberdayaan Masyarakat (Evaluasi Program Pengabdian Kepada Masyarakat Tematik Pemberdayaan Umat Stai Darussalam Nganjuk) - Idam Mustofa (Intizam, Jurnal Manajemen Pendidikan Islam, 2021)
The Al-Ghazali Islamic Foundation (YIGA) Krempyang Nganjuk with the deployment of the Darussalam Islamic Institute in da'wah through community service is interesting to evaluate. This study focuses on the evaluation management of da'wah strategies that are carried out in community service involving lecturers, students and graduates. The program evaluation design in this study used a descriptive qualitative evaluation approach using the principles of appropriateness and adequacy by using a purposive sampling technique. Data collection techniques used are documentation, interviews and observations. Data analysis used the CIPP evaluation model developed by Daniel Stufflebeam, consisting of context evaluation, input evaluation, process evaluation, and product evaluation. The results of data analysis show that the principles of service that have been successfully developed by students in the implementation of the service program are: the principle of partnership; benefit; and volunteerism. The principles of service that have not yet been fully fulfilled are the principle of participation; empowerment; and the interrelationship of science, charity and social transformation.